Value Chain Contraints of Dairy Industry toward Smallholder Farmer Development in Yogyakarta, Indonesia - Guntoro, Budi (2016)
The purpose of this study is to provide a comprehensive view of the value chain of dairy industry in Yogyakarta Province, and how to improve the value chain to improve market access. The specific objectives are: to identify the value chain constraints in the dairy industry, which is expected to find challenges and potential in the development of dairy farming in Yogyakarta province. Respondents were used in this study were dairy farmers located in Sleman, cooperatives, dairy processing industries, middlemen and consumers. Data collection tool by using a questionnaire that had been tested for validity and reliability. Primary data collection used two techniques, namely observation; collecting data by observing directly the object of research, and interviews; namely the collection of data by requesting information from the respondents, mapping the value chain analysis determined the general approach to the analysis of the value chain, the method of bottom-up and top-down. The data were analyzed using descriptive analysis. The results showed that the dairy value chain / industry on milking line of Yogyakarta was combined distribution channels of various dairy products from producers (farmers), processing, and marketing. Value chain requires that the addition of the value of the product every passing activity (line). At the farm level had not found that all farmers have an activity to raise the value of a product (milk). At the cooperative level: in addition to milk, value added through pasteurization, cheese, yogurt. At the milk processing industry: processing of products into a wide variety of processed milk powder, formula, cereal, baby food, dietary supplements, either alone products, the product license, and its subsidiaries. Retailers: milk, heating milk (3 times the base price of milk). Advanced retailers: processing milk into yogurt, heating, and kefir.